Aplikasi Berbagai Pupuk Pelengkap Cair dan Pupuk Kandang Ayam terhadap Peningkatan Produksi Sawit (Brassica juncea L.) - Elza Zuhry; Armaini ' (Universitas Riau, 2009)
The objective of this research was to determine the best of liquid complement fertilizer and chicken manure application in increasing Brassica juncea production. This research was carried out in Organic Agriculture Plot, Faculty of Agriculture, Riau University . The experiment used Completely Randomized Design with two factors. The first factor was liquid complement fertilizer which consists of 3 levels (without liquid complement fertilizer, Bayfolan and Gardena). The second factor was chicken manure, which consists of 4 levels (without chicken manure, 5 ton/ha, 10 ton/ha, and 15 ton/ha). The analysis of variance will be continued with Duncan New Multiple Range Test. The result of this research showed that the application of combined Bayfolan in 3 cc/l water with 15 ton/ha chicken manure influence all parameters measured which are height of plant, the number of leaf, leaf width, production of the plant, weight of the plant, chlorophyll analysis and plant growth rate.